2004
DOI: 10.1046/j.1445-2197.2003.02909.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic stapling for pharyngeal pouch: does it make the cut?

Abstract: The early experience of endoscopic stapling for pharyngeal pouch in Adelaide is encouraging. The procedure achieves excellent control of symptoms and can be undertaken with minimal morbidity. Recurrence may be a problem, although repeat endoscopic stapling can be undertaken without difficulty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…One issue in the assessment of recurrence is the definition. Some authors have found that while a pouch may be present, the symptoms have reduced substantially 13 , 16 . Patients will often report improvement (such that food no longer sticks) and satisfaction with the procedure, but some difficulties with swallowing (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…One issue in the assessment of recurrence is the definition. Some authors have found that while a pouch may be present, the symptoms have reduced substantially 13 , 16 . Patients will often report improvement (such that food no longer sticks) and satisfaction with the procedure, but some difficulties with swallowing (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 6,915 patients from 93 studies evaluating the effect of the surgical treatment for ZD, including 52 studies [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59] (n = 3,336) on endoscopic surgeries, 22 [60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81] (n = 2,204) on open surgeries, and 19 [3,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,…”
Section: Search Resultsmentioning
confidence: 99%
“…All patients with a symptomatic pharyngeal pouch who were deemed safe to undergo general anaesthesia were offered a cricopharyngeal myotomy via an endoscopic or transcervical approach. These techniques are described elsewhere [4, 8]. During an open approach, the pharyngeal pouch was either left alone, suspended, or excised.…”
Section: Methodsmentioning
confidence: 99%
“…A pharyngeal pouch frequently affects elderly patients, resulting in dysphagia, aspiration pneumonia, malnutrition, and poor quality‐of‐life [3]. Treatment involves division of the cricopharyngeal muscle, which can be accomplished endoscopically or by open neck surgery [3, 4]. Through a transcervical approach, the pouch can be suspended or excised to minimize accumulation of liquids and solids [3].…”
Section: Introductionmentioning
confidence: 99%